Effect of hydrofluoric acid on glucose metabolism of the mouse studied by whole-body autoradiography. Issue 4 (November 1975) - Watanabe, M; Yoshida, Y; Watanabe, M; Shimada, M; Kurimoto, K
Abstract : Distribution of radioactive carbon from [U-14C]glucose in the mouse poisoned by hydrofluoric acid has been studied by whole-body autoradiography. Under normal conditions, the highest autoradiographic density was found in the Harder's gland, palatine gland, sublingual gland, large intestinal mucosa, and many regions of the central nervous system 30 minutes after intraperitoneal injection of [U-14C]glucose. On the other hand, after hydrofluoric acid poisoning, it was found that (1) the radioactivity of brain was unchanged throughout all the poisoning; (2) the liver, renal cortex, lung, and blood showed an increase in radioactivity at 180 minutes of poisoning; (3) the abdominal cavity showed a tendency to residual radioactivity with the poisoning; (4) by contrast, Harder's gland, the palatine gland, sublingual gland, and large intestinal mucosa showed a decrease in radioactivity at 180 minutes of poisoning.